2018
DOI: 10.1089/ars.2017.7299
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and Immunometabolism in Diabetes and Aging

Abstract: Significance: A strong relationship between hyperglycemia, impaired insulin pathway, and cardiovascular disease in type 2 diabetes (T2D) is linked to oxidative stress and inflammation. Immunometabolic pathways link these pathogenic processes and pose important potential therapeutic targets.Recent Advances: The link between immunity and metabolism is bidirectional and includes the role of inflammation in the pathogenesis of metabolic disorders such as T2D, obesity, metabolic syndrome, and hypertension and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 183 publications
(282 reference statements)
1
47
0
2
Order By: Relevance
“…While over nutrition is known to drive chronic metabolic inflammation, also dysbiosis with the increased release of inflammatory products contribute to inflamm-aging [25]. Ultimately, chronic low-grade inflammation and immune response lead to accelerated aging processes [170]. This glycan interaction explanation for immune and inflammatory processes is not meant to substitute the previously confirmed ABO-food interaction (food lectins binding to human glycoconjugates) but to be supplementary to it.…”
Section: Glycan Reactionsmentioning
confidence: 99%
“…While over nutrition is known to drive chronic metabolic inflammation, also dysbiosis with the increased release of inflammatory products contribute to inflamm-aging [25]. Ultimately, chronic low-grade inflammation and immune response lead to accelerated aging processes [170]. This glycan interaction explanation for immune and inflammatory processes is not meant to substitute the previously confirmed ABO-food interaction (food lectins binding to human glycoconjugates) but to be supplementary to it.…”
Section: Glycan Reactionsmentioning
confidence: 99%
“…In addition an intriguing view is presented by Paula Neto et al that food additives, which normally are considered harmless, can affect immune system cells that in turn modulates metabolic deregulations like obesity and diabetes. This notion is strengthened by the view that both immune disorders and abnormal metabolic states affect each other in bidirectional way, and more often than not immune activation leads to metabolically abnormal state which may be controlled by epigenetic mechanisms …”
Section: Immunometabolism In Metabolic Deregulationmentioning
confidence: 99%
“…This notion is strengthened by the view that both immune disorders and abnormal metabolic states affect each other in bidirectional way, and more often than not immune activation leads to metabolically abnormal state which may be controlled by epigenetic mechanisms. 12 Key evidence regarding the metabolic alteration within immune system and its implication on lipid metabolism is provided by Shubham et al recently. Study revealed that arachidonic acid, sphingolipid and glycosphingolipid metabolic pathways were upregulated in visceral adipose tissues (VAT) of non-alcoholic fatty liver disease (NAFLD) and this phenomenon coexisted with pro-inflammatory bias in these patients.…”
Section: Immunometabolism In Metabolic Dere Gulationmentioning
confidence: 99%
“…EDNRA обладает высокой аффинностью к EDN1 и EDN2, но слабо связывается с EDN3, тогда как EDNRB демонстрирует схожую аффинность ко всем лигандам [4]. Активация EDNRA и EDNRB опосредует многие важные эффекты эндотелинов, включая вазоконстрикцию, ремоделирование сосудов, прооксидантный и провоспалительный эффекты, пролиферацию и дифференцировку клеток [5]. Кроме того, эндотелины стимулируют секреторную активность клеток фибробластического ряда, повышают продукцию и накопление коллагена, регулируют продукцию адипокинов и липолиз в белых адипоцитах, модулируют чувствительность клеток к инсулину [8].…”
Section: Introductionunclassified